Labour Market of Ukraine and Meeting Post-War Workforce Supply Market Demands - Kulishov, Volodymyr; Herasymenko, Yuliia; Furs, Oleg; Pakhomov, Ilya (Dr. Viktor Koval, 2024)
Introduction. Full-scale military actions in Ukraine increased the dynamics of changes in the labour market, caused significant uncertainty in influencing factors, and increased the imbalance of supply and demand in the labour market, which was characterised as a crisis even before the invasion. This strengthened the need for a relevant assessment of the needs of the Ukrainian labour market and the possibility of its personnel support and management of labour resources, taking into account the risks for the country's economy and post-war reconstruction. Aim and tasks. The purpose of this article is to evaluate the labour market of Ukraine in the post-war period and substantiate ways of meeting the market's personnel needs using the example of the construction and IT industries. The tasks of this study are to identify the factors affecting the labour market in the post-war period, assess the dynamics of changes in the balance of demand and supply in the labour market in the post-war period, and develop a mathematically formalised approach to the adaptive assessment of the labour market. Results. The developed mathematically formalised approach to assessing the imbalance of the labour market in individual areas allowed the stabilisation of the demand and supply of the IT labour market in 2026 at a level 1.496 times lower than the maximum in 2023. In the construction industry, differentiation in sectoral priorities of post-war reconstruction has been determined, as evidenced by the expected shortage of personnel in this industry, which is 2.15 times higher than the indicator for all industries. This is also indicated by the differentiation in the demand for qualified workers from 20% to 60% for large and small construction enterprises. Conclusions. The identified reasons for the uncertainty of factors affecting the labour market (losses in the quality of labour resources and forced migration) proved that post-war reconstruction would require an adaptive approach to managing labour resources at all levels. The lack of personnel in the post-war period will require a change in the concept of ensuring the competitiveness of domestic enterprises by using cheap labour.    It was determined that the demand for qualified personnel in the post-war period for all industries would grow, which is confirmed by the dynamics of the index of change of employees, which is 30% higher for qualified workers than unskilled workers. Significant differentiation by micro-specialty influences the gap between demand and supply, which does not consider the market's needs.